Implementation of Optimized Soil Improvement Techniques for a Giga Project - Hamidi, Babak; Varaksin, S.; Nikraz, Hamid (American Society of Civil Engineers, 2010)
One of the world's largest ground improvement projects that has ever been carried out in one phase by a single specialist ground improvement contractor is the 2,600,000 m2 King Abdulla University of Science and Technology in Jeddah. What has made this project perhaps one of the most unique ground improvement accomplishments ever is not only its size but also the ability to interpret the ground conditions based on limited geotechnical investigation and the ground's behavior during the treatment, the know-how to adapt the solution to late architectural and structural changes, and the capacity to execute the works by an optimized combination of Dynamic Compaction, Dynamic Replacement, High Energy Dynamic Replacement and Dynamic Surcharging.